Inflammatory myofibroblastic tumor: A multi‐institutional study from the Pediatric Surgical Oncology Research Collaborative. Issue 7 (15th June 2022) - Rich, Barrie S.; Fishbein, Joanna; Lautz, Timothy; Rubalcava, Nathan S.; Kartal, Tanvi; Newman, Erika; Wok, Pei En; Romao, Rodrigo L. P.; Whitlock, Richard; Naik‐Mathuria, Bindi; Polites, Stephanie F.; Løfberg, Katrine; et al.
Abstract: Inflammatory myofibroblastic tumor (IMT) is a mesenchymal neoplasm of intermediate malignancy. We describe the largest cohort of IMT patients to date, aiming to further characterize this rare, poorly understood tumor. This is a multi‐institutional review of IMT patients ≤39 years, from 2000 to 2018, at 18 hospitals in the Pediatric Surgical Oncology Research Collaborative. One hundred and eighty‐two patients were identified with median age of 11 years. Thirty‐three percent of tumors were thoracic in origin. Presenting signs/symptoms included pain (29%), respiratory symptoms (25%) and constitutional symptoms (20%). Median tumor size was 3.9 cm. Anaplastic lymphoma kinase (ALK) overexpression was identified in 53% of patients. Seven percent of patients had distant disease at diagnosis. Ninety‐one percent of patients underwent resection: 14% received neoadjuvant treatment and 22% adjuvant treatment. Twelve percent of patients received an ALK inhibitor. Sixty‐six percent of surgical patients had complete resection, with 20% positive microscopic margins and 14% gross residual disease. Approximately 40% had en bloc resection of involved organs. Median follow‐up time was 36 months. Overall 5‐year survival was 95% and 5‐year event‐free survival was 80%. Predictors of recurrence included respiratory symptoms, tumor size and distant disease. Gross or microscopic margins were not associated with recurrence, suggesting that aggressive attempts at resection may not be warranted. Abstract : What's new? Inflammatory myofibroblastic tumor (IMT) is a heterogeneous malignancy with variable patterns of histology and behavior that primarily affects children and young adults. Owing to its rarity, however, IMT remains poorly understood. Here, data from a multi‐institutional retrospective review of children and young adults with IMT was assessed to identify novel characteristics and thereby advance understanding of IMT. Analyses reveal a 5‐year recurrence rate of 20%, wherein respiratory symptoms, tumor size and metastatic disease were linked to recurrence. Moreover, positive surgical margins did not correlate with event‐free survival, calling into question the role of aggressive surgical resection in IMT.